(untitled) (Journal of Emerging Technology in Teaching and Learning (JETTLe), 2025)
This study investigates the effectiveness of implementing project-based learning through the Learning Management System (LMS) in enhancing students’ science process skills in the "Science and Technology" course. Employing a quasi-experimental pretest-posttest design, the research involved students from the elementary school teacher education study program at Universitas PGRI Semarang. The findings indicate a significant improvement in students’ observation, experimentation, data analysis, and problem-solving skills after the implementation of project-based learning through LMS. These results highlight the potential of LMS as an effective learning model to enhance students’ competencies in science and technology courses. This study benefits students, lecturers, higher education institutions, and researchers in education by providing insights into innovative teaching strategies that leverage digital learning platforms.